THE INFLUENCE OF THE APPLICATION OF ETHNOMATHEMATICS IN THE CONTEXT OF THE TRADITIONAL ENGKLEK GAME ON THE MATHEMATICS LEARNING OUTCOMES OF CLASS IV STUDENTS AT PADEMONEGORO SUKODONO ELEMENTARY SCHOOL - Nur Sri; Mohammad Faizal Amir (Universitas Cokroaminoto Palopo, 2026)
The process of learning mathematics at the elementary school level still faces challenges, especially in understanding abstract concepts, which results in poor learning outcomes for students. Several ways to address this problem include implementing an ethnomathematics approach to connect mathematical ideas with local cultural wisdom, such as playing the traditional game of engklek. This study aims to measure the impact of applying ethnomathematics related to the traditional game of engklek on the mathematics learning targets of fourth-grade students at SDN Pademonegoro Sukodono. This study adopts a quantitative method with a pre-experimental design of the one-group pretest-posttest type. The number of research samples was 23 students obtained using purposive sampling. Data collection was carried out using pretest and posttest tests. Data analysis included normality testing, hypothesis testing using the Wilcoxon test, and N-Gain calculations to determine the level of improvement in learning outcomes. The research findings showed that the average pretest score, which was initially 45.22, increased to 86.52 at the posttest. Hypothesis testing showed a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference between before and after the treatment. The average N-Gain value reached 0.6558, which is in the moderate category. Therefore, the application of ethnomathematics through the engklek game.